Time for the Ancients : Measurement, Theory, Experience - Singer, P. N. (2022)
The book offers an overview of experiences, theories and conceptions of time in the Graeco-Roman world. It presents the results of new research on neglected medical texts, relating to time management, aging and times of life, and the importance of the accurate time assessment. At the same time it draws together the most important findings of much recent classical scholarship on ancient attitudes to time, and presents them in accessible form.